Famine, philanthropy and the colonial state North India in the early nineteenth century - Sharma, Sanjay (Oxford University Press, 2001)
This book examines the lesser known aspects of the colonial state through the lens of the many famines and famine induced crimes which affected north India as it emerged from the 'chaotic' 18th century. It situates the 1837-8 famine in the political, ideological and economic processes of the colonial state which, paradoxically, continued to advocate laissez faire even as its humanitarian and pragmatic concerns (including fears of disorder) resulted in a series of interventionist policies
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Geschichte 1780-1840; Geschichte; Politik; Charity organization -- India -- History; Famines -- India -- Ganges-Yamuna Doab -- History; Food relief -- India -- Ganges-Yamuna Doab -- History; Nahrungsmittelhilfe; Hungersnot; Indien; India -- Politics and government -- 19th century; Indien -- Nord; Hochschulschrift